Relevance theoretic approach to the particle 'hina' in Koine Greek - Sim, Margaret Gavin (The University of Edinburgh. College of Humanities and Social Science. School of Divinity, 2006)
This thesis uses insights from a modern theory of communication, Relevance Theory, to examine the function of certain particles - in particular the conjunction hina - in Koine Greek. This particle has been regarded from the time of Classical Greek as an introducer of purpose clauses and so has been thought to have the lexical meaning of ‘in order that.’ More recently, however, scholars have recognised that in the New Testament at least, no more than 60% of the uses of hina merit such a translation, with a considerable number of independent clauses being introduced by this particle also. Apart from the New Testament it is the case that pagan writers of Koine used this particle to introduce a wider range of clauses than merely those with a telic relationship to the main clause of the sentence. This is particularly noticeable in the Discourses of Epictetus, a philosopher who taught in the latter half of the first century of the Christian era. In addition, Dionysius of Halicarnassus, a notable critic of literary style and the historian Polybius, both writing within the Koine period used hina to introduce indirect commands and noun clauses as well as purpose clauses. The frequency of such uses (approximately 10% of all the instances of this particle) in their writings is considerably less than that of Epictetus, but those uses are nevertheless present in their works. Since iota-nu-alpha was used for this wider range of clauses by pagan, non-Jewish authors, some of whom spoke Greek as their first language, it seems extremely implausible to attribute such use to the incompetence of the implied authors of the New Testament, or ‘Semitic interference’. Since the many instances of non-telic hina in the New Testament are identified with reference to the context in which they occur, the telic instances should also be deduced from such context. I claim that the function of this particle is not to introduce a purpose clause nor does it have a fixed lexical meaning of ‘in order that’, but rather that it alerts the reader to expect an interpretation of the thought of the speaker or implied author. Of course in many instances a clause introduced by hina will be a purpose clause, but this is inferred from context rather than solely from the presence of this particle. This thesis proposes a unified account of the function of hina which fits the developing pattern of the language and relates it to the particle o(/ti, and provides a theoretical basis for its use as an indicator of speaker or subject’s thought, thus enabling a reader to re-examine biblical texts whose interpretation has been problematic to date.
A relevance theoretic approach to the particle 'hina' in Koine Greek
Keywords: divinity; PhD thesis; Relevance Theory; Koine Greek; New Testament